Determining The Optimum Inventory Of Mujaerr Using The Newsboy Method (Case Study At Pt. Xyz) - Pungky Suherman; Ribangun Bamban Jakaria (Universitas Muhammadiyah Sidoarjo, 2021)
Tilapia fish is a freshwater fish commodity that has quite a lot of nutritional content so that there are many devotees. PT. XYZ provides an adequate supply of tilapia fish, but there are many complaints from customers about the availability of this fish so they are demanded to continue conduct an evaluation of the fish stock. the fishmonger must decide how much fish to buy from the supplier. If the fish seller buys too much fish and it doesn't sell out on that day, then the large number of fish that are not sold has no value on that day. Conversely, if the fish seller buys too little fish, then the seller fish have lost the opportunity to get a bigger profit. This study aims to optimize the supply of mujaer fish. The method in research using the newsboy method, data collection methods used are by using observation, interviews and data processing. You will know the amount of fish stock for the day Monday to Friday as much as 3000 kg, this calculation is based on the results of data patterns, trend analysis and the average fish sold, it can be concluded that Monday-Friday supplies can generate optimum profit.